Immobilization of metal–humic acid complexes in anaerobic granular sludge for their application as solid-phase redox mediators in the biotransformation of iopromide in UASB reactors. (May 2016) - Cruz-Zavala, Aracely S.; Pat-Espadas, Aurora M.; Rangel-Mendez, J. Rene; Chazaro-Ruiz, Luis F.; Ascacio-Valdes, Juan A.; Aguilar, Cristobal N.; Cervantes, Francisco J.
Highlights: Metal–humic acid complexes were immobilized by a granulation process. Immobilized humic complexes enhanced the biotransformation of iopromide. Deiodination, N-dealkylation, decarboxylation and deacetylation occurred. First application of immobilized redox mediator without a supporting material. Redox catalyst suitable for enhancing degradation of recalcitrant pollutants. Abstract: Metal–humic acid complexes were synthesized and immobilized by a granulation process in anaerobic sludge for their application as solid-phase redox mediators (RM) in the biotransformation of iopromide. Characterization of Ca- and Fe-humic acid complexes revealed electron accepting capacities of 0.472 and 0.556 milli-equivalents g −1, respectively. Once immobilized, metal–humic acid complexes significantly increased the biotransformation of iopromide in upflow anaerobic sludge blanket (UASB) reactors. Control UASB reactor (without humic material) achieved 31.6% of iopromide removal, while 80% was removed in UASB reactors supplied with each metal–humic acid complex. Further analyses indicated multiple transformation reactions taking place in iopromide including deiodination, N-dealkylation, decarboxylation and deacetylation. This is the first successful application of immobilized RM, which does not require a supporting material to maintain the solid-phase RM in long term operation of bioreactors. The proposed redox catalyst could be suitable for enhancing the redox conversion of different recalcitrant pollutants present in industrial effluents.